Auricular Acupressure for Managing Postoperative Pain and Knee Motion in Patients with Total Knee Replacement: A Randomized Sham Control Study. (10th July 2012) - Chang, Ling-hua; Hsu, Chung-Hua; Jong, Gwo-Ping; Ho, Shungtai; Tsay, Shiow-luan; Lin, Kuan-Chia
Abstract : Background . Postoperative pain management remains a significant challenge for all healthcare providers. A randomized controlled trial was conducted to examine the adjuvant effects of auricular acupressure on relieving postoperative pain and improving the passive range of motion in patients with total knee replacement (TKR). Method . Sixty-two patients who had undergone a TKR were randomly assigned to the acupressure group and the sham control group. The intervention was delivered three times a day for 3 days. A visual analog scale (VAS) and the Short-Form McGill Pain Questionnaire were used to assess pain intensity. Pain medication consumption was recorded, and the knee motion was measured using a goniometer. Results . The patients experienced a moderately severe level of pain postoperatively (VAS 58.66 ± 20.35) while being on the routine PCA. No differences were found in pain scores between the groups at all points. However, analgesic drug usage in the acupressure group patients was significantly lower than in the sham control group (P < 0.05 ), controlling for BMI, age, and pain score. On the 3rd day after surgery, the passive knee motion in the acupressure group patients was significantly better than in the sham control group patients (P < 0.05 ), controlling for BMI. Conclusion . The application of auricular acupressure at specific therapeutic points significantly reduces the opioid analgesia requirement and improves the knee motion in patients with TKR.